Nutritive Value of the Crab Podophthalmus vigil (Fabridrus) - RADHAKRISHNAN, C K; NATARAJAN, R (Fishery Technology, 2017)
Among the edible crabs, Podophthalmus vigil occupies a distinct position in PortoNovo coast. Though the fishery is seasonal, P. vigil supports an additional crabfishery from August to October. An attempt has been made to evaluate the nutritionalstatus of different size groups of P. vigil. It has been observed that proteinand moisture values are more in smaller crabs, corresponding with a drop in carbohydrateand fat. In bigger size groups, the values of fat and carbohydrate are foundto be higher, while protein and moisture contents decreased slightly. The totalmeat content varies in different crabs of the same size group and theaverage value of the total consumable part is found to be only less than 30% of thetotal weight of the animal.